The Design and Building of Medium Capacity Drying House for Bokar - Sri Aulia Novita; Hendra Hendra; Perdana Putera; Fithra Herdian; Muhammad Makky; Khandra Fahmi (Journal of Applied Agricultural Science and Technology, 2021)
Bokar, processed rubber material, is latex obtained from rubber trees of community plantations. The quality of latex can be identified from its features which are white, relatively soft, and odorless. The purpose of this research was to design a simple rubber sheet drying house and examine the quality of dry rubber under Indonesian National Standard. Bokars are processed using a liquid smoke coagulant with a concentration of 10-15% and it obtained a clean white rubber although it has a slight smoke smell. Before drying, Bokar had ground to gain the thickness of the unsmoked sheet/ USS around 3-5 mm. The components of the drying house include the drying room, heating room, heater, thermometer, blower, plenum chamber, ventilation, drying room door, and electric motor. The capacity of the drying house is 200 kg of rubber sheet, with a drying temperature of 35 – 46oC and 6 hours drying time. The rubber produced has good quality with average dry rubber content (DRC) was 73.75%.